360-degree video in education: An overview and a comparative social media data analysis of the last decade - Georgios Lampropoulos; Vassilis Barkoukis; Kevin Burden; Theofylaktos Anastasiadis (Smart Learning Environments, 2021)
Abstract Due to its immersive and interactive nature, 360-degree video is becoming ever more popular. However, little is known about the public’s viewpoints and attitudes regarding the use of this emerging technology in educational contexts. This study reviews the research evidence for 360° video, virtual learning environments and social media and presents related studies. Moreover, the methodology, the tools and the analysis process used to comparatively analyze social media data are presented and the results that arose are showcased. The use of 360° video in education is discussed and directions for future research are given. Based on the data from the last 10 years, the main findings of the study show that 360° video and its use in educational settings are recognized positively by the public who mostly express anticipation, trust and joy when referring to it. Nonetheless, teachers are unfamiliar with 360° video and do not have the necessary technical skills to develop educational material using it or incorporating it into teaching activities. Finally, 360° video is proven to be an effective educational tool which satisfies the emerging educational needs, enriches the teaching and learning process and promotes students’ motivation, active participation and engagement, rendering, thus, learning more effective.